A Picture is Worth a Thousand Words: Road Maps as Analytical Tools - Alegant, Brian (Current Musicology, 2013)
A road map is a representation or documentation of how one hears a work unfold in time. In its simplest form, a road map can be a time line or flow chart. But it can also be an elaborate landscape of observations, correspondences, and associations, with text descriptions, symbols, staff notation, rhythms, colors, and shapes. A road map can be teleological or non–linear; literal or abstract; monochromatic or multi–colored; sparse or dense; small or large; hand–drawn or created with a music notation program such as Sibelius or Finale. I would argue that a road map—like any piece of writing—is provisional. There is no right or wrong way to create one, although some maps are definitely more compelling, thoughtful, and musical than others. The idea behind a road map is to capture the important characteristics of a work and represent them in some way that makes sense. For this reason I occasionally ask students to re–map the same work later in a semester. The results often reveal (to student and instructor alike) significant refinement in hearing and sophistication in modeling. A map can trace the history of pitches, pitch–classes, set–classes, rhythms, gestures, themes, registers, dynamics, articulations, texture and other parameters; it can highlight phrase structures, structural upbeats and downbeats, and climaxes; and it can model formal organization and energy flow, character, compositional strategies, and narrative. Road maps facilitate deeper engagement with music, foster critical listening skills, and provide a creative outlet for students, especially those who are visual learners.